The Need for a Sexual Assault Nurse Examiner - Gökdoğan, Mira R (The Bulletin of Legal Medicine, 2008)
Sexual offenses are recognized to be one of the most critical of crimes throughout the world. In Turkey, forcible rapes show a percentage of more than 3%, every year. It become even more critical when realizing that less than half of all rapes believed to occur are reported to law enforcement, and of those assailants arrested even fewer are convicted of rape. Often, fear of humiliation, and lack of support in society are the reasons for non-accusation. On the other hand, little or no knowledge of the correct methods of locating, recovering, packaging, and preserving evidence specimens are the causes for compromising the forensic examination in court. This problem occurs when medical personnel are not adequately trained or properly advised in the evidentiary aspects and medical features of treating a victim. This paper presents the results of a study to determine the likelihood of obtaining corroborating evidence. An updated questionnaire has been applied at random on medical personnel, a total of 543 participants, throughout Turkey. Taking certain criteria into consideration the findings revealed a significant deficiency of knowledge regarding medical-legal examination. In comparison, a one-semester course of basic forensic nursing proved to be sufficient to recognize the amount of knowledge required to work as a forensic professional. Based on the results, recommendations are presented in form of a SANE. This specialized area of forensic nursing has engendered a new type of sexual assault professional, namely, the Sexual Assault Nurse Examiner (SANE). SANEs are nurses who have undergone extensive training qualifying them to provide comprehensive medical care and forensic collection services without physician involvement. The primary objective of the SANE model is to increase the efficiency, consistency, and quality of health care and evidence collection by using a single well trained professional. This will be the first step in building a responsible and successful evidence collection program that will survive the rigors of courtroom challenge. Key words: Forensic nursing, SANE, sexual assault, evidence collection, Turkey